2015
DOI: 10.1002/elan.201500235
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Cathodic Stripping Voltammetric Method for Determination of Gallium Using an In Situ Plated Lead Film Electrode

Abstract: 1IntroductionOver the last few decades,g alliumc ompounds have gained importance in the fields of electronics and medicine.I nm edicine severalg allium salts are useda sb oth pharmaceuticals and radiopharmaceuticals.I nc linical medicine,r adioactive galliuma nd stable gallium nitrate are used as diagnostic and therapeutic agents in cancer and disorders of calcium and bone metabolism [1,2].I n electronics,t he most commona pplications for gallium include advanced semiconductors for microwave transceivers,D VDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Ga [67] and Cr [68]. These methods are developed using common carbon paste 116 electrodes [60;61] or screen-printed ones [69;70], but also use more recent substrates 117 such as e.g.…”
Section: List Of Nomenclature and Abbreviationsmentioning
confidence: 99%
“…Ga [67] and Cr [68]. These methods are developed using common carbon paste 116 electrodes [60;61] or screen-printed ones [69;70], but also use more recent substrates 117 such as e.g.…”
Section: List Of Nomenclature and Abbreviationsmentioning
confidence: 99%
“…& pH and concentration of the supporting electrolyte, & the concentration of the complexing agent, & the potential and time of accumulation of the indium and gallium complexes at the working electrode surface had to be chosen so as to obtain optimal signals concomitantly for both analyzed elements, considering the height, shape of the peaks, and their separation on the voltammogram. Previous studies showed that Ga(III) and In(III) form electrochemically active complexes with cupferron, which allow voltammetric determination of these elements with a low limit of detection [19,25,26,32]. The choice of the working electrode was directed to provide the best sensitivity, and as we know, this can be obtained using mercury electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…[145] The in situ plated Pb film electrode could be also utilized to detect Ga(III) by AdCSV, for which a linear sensing profile ranging from 1 × 10 −8 to 2 × 10 −7 mol L −1 was reported with a detection limit of 0.209 ppb, which was relatively higher than that of a hanging Hg drop electrode from previous reports. [146] The same Pb film was used to measure trace metal of In(III) by AdSV, resulting in a 5 × 10 −10 to 2 × 10 −7 mol L −1 sensing range and the lowest detection limit of 0.0138 ppb reported to date. [147] Researchers utilized a combination of SEM and AFM imaging and XRD to study the morphology of Pb crystallites deposited on glassy carbon substrate forming the active electrode.…”
Section: Lead-based Electrodesmentioning
confidence: 99%